Factors Influencing Accountability of Public Sector Organization Performance Learning Study in Kadiri Regency - Meme Rukmini; Duwi Riningsih; Bima Fatkul Khusna; Rafa Hylmi Musyafar (Electronic Journal of Education, Social Economics and Technology, 2026)
The purpose of this study is to investigate the elements that influence Kediri Regency's public sector organizations' performance accountability.  The study mainly looks into how organizational responsibility is affected by accounting control, reporting systems, legal and regulatory compliance, financial officers' accounting knowledge, and financial management information systems.  A quantitative method was used, combining partial least squares (PLS) analysis with the Structural Equation Modeling (SEM) technique.  The results show that performance accountability in public sector organizations is significantly impacted by accounting control and reporting systems. The accounting proficiency of financial officers and adherence to regulatory requirements also have a beneficial, if smaller, impact.  Although the financial management information system contributes to increased accountability and openness, its impact is comparatively less significant than that of the other elements.  Furthermore, the study finds that strengthening public sector accountability requires key components like effective leadership, engaged community involvement, and the growth of human resource skills.  For the Kediri Regency local government, these findings provide insightful information that emphasizes the necessity of consistently bolstering financial systems, reporting protocols, and control mechanisms in order to increase accountability and transparency in the provision of public services.